Adsorption of Metal (Cd) from Wastewater by Plant Material (Crotalaria burhia) - Himmat Singh Panwar; Vinod Vaishnav; Kailash Daga (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Cadmium is a highly toxic inorganic pollutant whose emission sources are widely diffused, giving rise to a large scale environmental pollution. Cadmium is one of the most toxic metals even in low concentrations. It is naturally produced in the environment and is a major contaminant. Cadmium (Cd) toxicity causes disorders such as heart disease, cancer and diabetes. The major objective of this paper was to investigate the removal of Cadmium (II) from wastewater using activated carbon prepared from leaves of Crotalaria burhia(AC-CB) an unconventional adsorbent. The dried leaves of Crotalaria burhia plant were used at different adsorbent/metal ion ratios. The influence of pH, contact time, metal concentration, and adsorbent loading weight on the removal process was investigated. Batch adsorption studies were carried out at room temperature. Removal efficiency increased with an increase in contact time before equilibrium is reached. The adsorption data fit well with the Langmuir and Freundlich isotherm models. This research focuses on understanding adsorption process and developing a cost effective technology for treatment of heavy metals-contaminated industrial wastewater. Comprehensive characterization of parameters indicates Crotalaria burhia to be a good material for adsorption of Cd (II) to treat wastewaters containing low concentration of the metal.